PERBANDINGAN HASIL ANALISA FOTO HOAX MENGGUNAKAN METODE EXIF/METADATA, REVERSE IMAGE DAN FORENSICS - Moh Subli; Muhamad Masjun Efendi; Salman Salman (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
The hoax information that has been spread so far is in the form of photos that have been edited and manipulated from actual photos, then the photos are spread widely on the internet. The development of increasingly advanced photos makes it have many advantages to be used as hoax news, such as easy to manipulate, easy to spread massively and widely and easy to make people believe quickly. Changes in photos that are easily manipulated can change the information submitted to be different and make them vulnerable to being used for crime. With many photos that are used as a means of crime, it is necessary to do a study that can be used as a guide to be able to see which photos are real and which are fake by using a method. There are so many circulating methods that can see the authenticity and fakeness of the photo. However, from many in circulation, it is not uncommon to have a level of testing that is not close to the truth, because the feasibility and level of truth of the method still cannot be trusted. For this reason, in this study, the results of the analysis of hoax photos are compared using the exif/metadata, reverse image and image forensics methods. These three methods will be used as examples of which one is closer to the truth which can then be used as a guide or reference by people to prove the authenticity of a photo or information that is being spread widely in the community.